A 90-day Bundled Payment for Primary Single-level Lumbar Discectomy/Decompression: What Does "Big Data" Say?. Issue 3 (April 2018) - Jain, Nikhil; Virk, Sohrab S.; Phillips, Frank M.; Yu, Elizabeth; Khan, Safdar N.
Abstract : Episode-based bundling may become the major form of reimbursement for many elective spine procedures. As the amount for a 90-day episode of care is not known for a lumbar discectomy, we analyzed the previous reimbursements from Commercial payers (2007–Q2 2015), Medicare Advantage (2007–Q2 2015), and Medicare (2005–2012) for a primary single-level lumbar discectomy/decompression. Distribution of payments among various service providers was studied and a 90-day bundle was simulated. Depending on the payer type, the average facility costs constituted 59.7% to 73.6% of total payments, followed by surgeon's fees, which accounted for 13.7% to 18.5%. Postacute services made up 8.8% to 15.8% of the total reimbursement. Surgeries performed in the inpatient setting were significantly more expensive as compared with surgeries performed in the outpatient setting ( P <0.01). The average 90-day bundle amount was estimated at $11, 091, $6571, and $6239 for Commercial payers, Medicare Advantage, and Medicare, respectively. Overall, service providers in the Southern region were reimbursed the lowest from Commercial payers and Medicare, compared with other regions. Postacute services are not as major cost drivers after discectomy as after total joint arthroplasty or hip fracture repair.